Pengaruh Pengendalian Internal dan Sistem Informasi Akuntansi Terhadap Kinerja Pegawai pada Inspektorat Daerah Kota Gorontalo - Nur Sabriani Kaaba; Nilawaty Yusuf; Muliyani Mahmud (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to determine the effect of internal control and accounting information systems on employee performance at the Gorontalo City Regional Inspectorate Office. The study uses a quantitative research method. The primary data source was obtained from a questionnaire distributed to State Civil Apparatus (ASN) at the Gorontalo City Regional Inspectorate. The data analysis technique in this study is descriptive quantitative analysis using the statistical t test, statistical f test and coefficient of determination test using IBM SPSS 27 for windows. The results of the study indicate that partially internal control and accounting information systems have a significant positive effect on Employee Performance at the Gorontalo City Regional Inspectorate. Then simultaneously internal control and accounting information systems have a significant effect on employee performance by 45.2% while the remaining 58.2% is explained by other variables not explained in this study.